Paleoenvironments along the Eastern Laurentide Ice Sheet Margin and Timing of the Last Ice Maximum and Retreat - de Vernal, Anne; Hillaire-Marcel, Claude (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1987)
ABSTRACTPalynological and isotopic analysis in a few deep-sea cores from the Labrador Sea reveals strong environmental changes related to the Late Pleistocene glacial fluctuations over eastern Canada. On the whole, the Labrador Sea was characterized by strong exchanges between North Atlantic water masses, Arctic outflows, and meltwater discharges from Laurentide, Greenland and lnuitian ice sheets. The penetration of temperate Atlantic waters persisted throughout most of the Late Pleistocene, with a brief interruption during the Late Wisconsinan. During this glacial substage, a slight but continuous meltwater runoff from the Laurentide ice margins grounded on the northern Labrador Shelf is indicated by relatively low 18O values and low-salinity (< 30‰) dinocyst assemblages. The calving of the ice margin, the melwater outflow and the subsequent dilution of surface waters offshore Labrador probably contributed to the dispersal of floating ice and, consequently, to a southward displacement of the polar front restraining the penetration of North Atlantic waters into the Labrador Sea. The advection of southern air masses along the Laurentide ice margins, shown by pollen assemblages, was favourable to abundant precipitation and therefore, high ice accumulation rates, especially over northern Labrador during the Late Wisconsinan. The déglaciation is marked by a brief, but significant, melting event of northern Laurentide ice shortly after 17 ka. The main glacial retreat occurred after ca. 11 ka. It allowed restoration of WSW-ENE atmospheric trajectories, increased phytoplanktonic productivity, and penetration of North Atlantic water masses into the Labrador Sea.